Mechanisms of genetically-based resistance to malaria (2010)
Malaria remains one of the most prevalent parasitoses worldwide. About 350 to 500. million febrile episodes are observed yearly in African children alone and more than 1. million people die because of malaria each year. Multiple factors have hampered the effective control of this disease, some of which include the complex biology of the Plasmodium parasites, their high polymorphism and their increasingly high resistance to antimalarial drugs, mainly in endemic regions. The ancient interaction between malarial parasites and humans has led to the fixation in the population of several inherited alterations conferring protection against malaria. Some of the mechanisms underlying protection against this disease are described in this review for hemoglobin-inherited disorders (thalassemia, sickle-cell trait, HbC and HbE), erythrocyte polymorphisms (ovalocytosis and Duffy blood group), enzymopathies (G6PD deficiency and PK deficiency) and immunogenetic variants (HLA alleles, complement receptor 1, NOS2, tumor necrosis factor-? promoter and chromosome 5q31-q33 polymorphisms). © 2010 Elsevier B.V.